OsPIN5b modulates rice (Oryza sativa) plant architecture and yield by changing auxin homeostasis, transport and distribution. (25th August 2015) - Lu, Guangwen; Coneva, Viktoriya; Casaretto, José A.; Ying, Shan; Mahmood, Kashif; Liu, Fang; Nambara, Eiji; Bi, Yong‐Mei; Rothstein, Steven J.
Summary: Plant architecture attributes such as tillering, plant height and panicle size are important agronomic traits that determine rice ( Oryza sativa ) productivity. Here, we report that altered auxin content, transport and distribution affect these traits, and hence rice yield. Overexpression of the auxin efflux carrier‐like gene OsPIN5b causes pleiotropic effects, mainly reducing plant height, leaf and tiller number, shoot and root biomass, seed‐setting rate, panicle length and yield parameters. Conversely, reduced expression of OsPIN5b results in higher tiller number, more vigorous root system, longer panicles and increased yield. We show that OsPIN5b is an endoplasmic reticulum (ER) ‐localized protein that participates in auxin homeostasis, transport and distribution in vivo . This work describes an example of an auxin‐related gene where modulating its expression can simultaneously improve plant architecture and yield potential in rice, and reveals an important effect of hormonal signaling on these traits. Significance Statement: How auxin homeostasis affects plant architecture and yield is poorly understood in crop plants. Here we show that suppressing expression of an ER‐localized auxin transporter, OsPIN5b, results in increased biomass and improved yield in rice.